If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3x + 54)(2x) = 180 Reorder the terms: x(54 + 3x)(2x) = 180 Remove parenthesis around (2x) x(54 + 3x) * 2x = 180 Reorder the terms for easier multiplication: 2x * x(54 + 3x) = 180 Multiply x * x 2x2(54 + 3x) = 180 (54 * 2x2 + 3x * 2x2) = 180 (108x2 + 6x3) = 180 Solving 108x2 + 6x3 = 180 Solving for variable 'x'. Reorder the terms: -180 + 108x2 + 6x3 = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + 108x2 + 6x3 = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(-30 + 18x2 + x3) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-30 + 18x2 + x3)' equal to zero and attempt to solve: Simplifying -30 + 18x2 + x3 = 0 Solving -30 + 18x2 + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 31=9t-13t+7 | | 19-13p=17p-8 | | (-3n+5)(-5.7)= | | 1.5+.3(h-6)=.8h+2 | | -[6x-(3x+5)]=-4-[4(2x-4)-3x] | | 37+3n=-2 | | (5y-4)(6y-7)= | | 5+2k=3k-3 | | (-8x^4+6x+3)+(2x^4-2x^2+7)= | | 10X^4-6X^3+8X^2=0 | | 22j+11=4j-7 | | q=1000+25p+q | | 6+1(8x+12)= | | X-366=314 | | 90=n+n-10 | | 11x-5-6x=6x-2 | | 2x+y=10x+90 | | x(3x+54)(2x)=360 | | -8+6x=2x+16 | | X=4x-3x-10 | | -30+-80= | | 11x-(2x-5)=32 | | 10x+4=12x-15 | | -.72x=-1.44 | | X-6x=-35 | | 6(5-8w)+12=54 | | 71+(-71)= | | 4(-3-y)-3(-3)=-7 | | 4(1x-6)+4=6x-6 | | 4x+6x-60=45-5x | | 90=x+13+x | | -11x-9=-64 |